79x-76=90

Simple and best practice solution for 79x-76=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 79x-76=90 equation:


Simplifying
79x + -76 = 90

Reorder the terms:
-76 + 79x = 90

Solving
-76 + 79x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '76' to each side of the equation.
-76 + 76 + 79x = 90 + 76

Combine like terms: -76 + 76 = 0
0 + 79x = 90 + 76
79x = 90 + 76

Combine like terms: 90 + 76 = 166
79x = 166

Divide each side by '79'.
x = 2.101265823

Simplifying
x = 2.101265823

See similar equations:

| x^2+20x+4800=0 | | 78x+76=89 | | x+84=-82 | | x-3=2(x-4) | | 34x-68=79 | | -18=3(3x-3) | | 5(5x+1)=-20 | | P^4-14p^2+40=0 | | -4x+28=-x+7 | | 57x-98=978 | | 45x+78=980 | | 45x+78=98 | | 2c^4-6c^3-12c^2+36c=0 | | 67x+34=173 | | 67x+34=67 | | 6x+43=55 | | 6x+43=45 | | 6x+43=345 | | 6x+43=34 | | 5x+8y=3965 | | 23x-5=34 | | 3x-y=10x+6 | | 5x-41=8x | | 75-30=45 | | (7x+4)(4x-7)= | | 25+75+-90=35 | | x^7+8=-64 | | (3x+5)(x-9)= | | 11x-8=24 | | -16=7b+12 | | 8x+6=0.75 | | (3x-4)(2x+3)=0findx |

Equations solver categories